- IN SILICO STUDY OF DERIVATIVE COMPOUNDS OF GALANGAL PLANTS AS ANTI-INFLAMMATORY - I Wayan Tanjung Aryasa; I Kadek Arya Sugianta (Jurnal Penelitian Pendidikan IPA, 2023)
A Inflammation is the basis of pathogenesis of several diseases, both degenerative and non-degenerative diseases. Galangal plants which are commonly found in Indonesia are commonly used as traditional medicines for several diseases and also have secondary metabolite compounds that are useful as anti-inflammatory. In this study, an in silico approach in the form of molecular docking has been applied to 5 compounds derived from the galangal plant to important inflammatory molecular targets such as the cyclooxygenase-2 (COX-2) receptor. Analysis of the biological activity of compounds derived from the galangal plant using the WAY2DRUG PASS prediction server. Prediction results of physicochemical properties of compounds derived from galangal plant using the SWISS-ADME server. This study aims to predict the ability of 5 compounds derived from the galangal plant to inhibit the COX-2 enzyme. Detailed information has been obtained using a molecular docking approach. Docking simulations for 5 compounds derived from the galangal plant have been carried out through the Autodock 4.2 application which is embedded in the MGL Tools 1.5.6 application. The molecular interactions of compounds derived from galangal against COX-2 receptors were visualized using Discovery Studio (Biova) software. Based on the results of the research that has been carried out, it can be concluded that the test compound Galanganal has the best affinity when compared to the compounds Galanganol A, Galanganol B, Galanganol C and Galangin. This can be seen from the bond free energy value of -8.98 kcal/mol and the inhibition constant of 261.59 nM. These results indicate that the Galanganal test compound has potential as an anti-inflammatory agent. However, further research is needed to study more compounds derived from the galangal plant to isolate the best conformation.